The intensity of kelp harvesting shapes the population structure of the foundation species Lessonia trabeculata along the Chilean coastline - Gouraguine, Adam; Moore, Pippa; Burrows, Michael T.; Velasco, Eliana; Ariz, Luis; Figueroa‑Fábrega, Luis; Muñoz‑Cordovez, Rodrigo; Fernandez‑Cisternas, Italo; Smale, Dan; Pérez‑Matus, Alejandro (My University, 2021)
Kelp are foundation species that support high levels of biodiversity and, either directly or indirectly provide a wide range of ecological goods and services to human society. In recent decades, due to the high demand for kelp-derived products such as alginate, commercial wild harvesting has increased, leading to declines of kelp biomass in some regions. Chile accounts for 40% of the global kelp harvest, with the subtidal kelp, Lessonia trabeculata being one of the main target species. Currently, however, there is a lack of information on how different degrees of harvesting intensity, governed by distinct management regimes and their enforcement influences L. trabeculata populations. Here we examined the effect different management regimes, characterised by distinct levels of exploitation of kelp and kelp-associated fauna, have on L. trabeculata density and morphology along ~ 1600 km of the Chilean coastline. The findings demonstrated that harvesting intensity likely influences both L. trabeculata density and morphology. Juvenile density of L. trabeculata was five times higher in the most harvesting-affected areas, while kelp morphology values, including holdfast diameter, number of stipes and total length, were always higher in the less-intensively harvested areas. Our study suggests that different degrees of protection can influence density and morphology of subtidal L. trabeculata populations, which in turn has important implications for the conservation of the kelp forest ecosystems and management of this important fishery.